A crise ambiental e a publicidade impressa: um estudo à luz do Modelo de Análise Modular - Fabiana Fernanda de Jesus Parreira (2010)
This research has as the main stimulus the growing transmission, in magazines of wide circulation in our country, of printed advertisements that approach the environmental degradation and the damage caused to the planet. Our hypothesis is that this increase in disclosure of the environmental crises points by the advertising sphere may reveal new strategies for an effective sense construction. That said, we intend to analyze three printed advertisements aired by the Brazilian magazine called Época in 2007. The three chosen advertisements deal with certain points about the environmental crisis and show traces of an ecological conscience. For the analysis of the interweaving of the ecological discourse and the advertising discourse, we have as theoretical-methodological support the Genevan model of discourse analysis the Modular Analysis Model (MAM) developed by Eddy Roulet and others. Our path of analysis is the reference module (situational dimension) and hierarchical module (textual dimension) and the elementary organization form called relational, in order to observe how the presence of the ecological discourse in the advertising scene may evoke certain world views and build interesting effects of meaning.